2008
DOI: 10.1378/chest.07-2546
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Role of Clinical and Laboratory Criteria To Identify Early Ventilator-Associated Pneumonia in Brain Injury*

Abstract: PCT may be a useful marker to predict which patients subsequently have early VAP. The CPIS could help as an early way to detect the patients with early VAP and who need further diagnostic testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
45
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 39 publications
5
45
1
1
Order By: Relevance
“…1). [18][19][20][21][22][23][24][25][26][27][28][29][30] All the studies identified were published between 1999 and 2010. The overall prevalence and mortality of VAP in the included studies were 48% and 37%, respectively.…”
Section: Study Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…1). [18][19][20][21][22][23][24][25][26][27][28][29][30] All the studies identified were published between 1999 and 2010. The overall prevalence and mortality of VAP in the included studies were 48% and 37%, respectively.…”
Section: Study Selectionmentioning
confidence: 99%
“…Figure 3C shows the forest plot of the diagnostic odds ratio. Twelve of the 13 studies are plotted as the confidence intervals of the odds ratio; the 2008 study by Pelosi et al 19 had an infinite odds ratio value. Figure 3D shows the summary receiver operating characteristic curve.…”
Section: Diagnostic Accuracy Of Cpis For Diagnosis Of Vapmentioning
confidence: 99%
See 1 more Smart Citation
“…Procalcitonin may be considered as a valuable biomarker for the diagnosis of bacterial infections, including VAP, where its levels are correlated with outcome [25,26]. Its usefulness for guiding antibiotic therapy has been shown in patients admitted for community-acquired respiratory tract infections [27][28][29].…”
mentioning
confidence: 99%
“…Procalcitonin increased the specificity of clinical pulmonary infection score to 100%. The author concluded that procalcitonin may be a useful marker to predict which patients subsequently have early ventilator-associated pneumonia [11]. Ramirez P et al made sequential measurement of serum procalcitonin level and the calculation of the simplified clinical pulmonary infection score in 44 patients mechanically ventilated for >48 hours with neither active infection for the duration or suspicion of ventilator-associated pneumonia.…”
Section: Discussionmentioning
confidence: 99%